The Role of Axillary Lymph Node Dissection Width and Radiotherapy in Axillary Vein Pathologies and Psychophysical Outcomes in Breast Cancer - Mujdat Turan; Ibrahim Burak Bahcecioglu; Sumeyra Guler; Sevket Baris Morkavuk; Gokhan Giray Akgul; Sebnem Cimen; Elif Ayse Ucar; Ebru Umay; Mehmet Mert Hidiroglu; Yasemin Ozkan; Mutlu Sahin; Kerim Bora Yilmaz (Medicina)
Background and Objectives: Lymphedema is one of the most important morbid complications of modified radical mastectomy (MRM) surgery. It can cause limb movement restriction and psychosocial deformities in some patients. This study aimed to determine and compare the physiological and pathological changes that develop in the axillary venous structures in patients who underwent axillary lymph node dissection (ALND) and sentinel lymph node biopsy (SLNB). Materials and Methods: Patients diagnosed with breast cancer who underwent MRM and breast-conserving surgery (BCS) plus SLNB between 2017 and 2022 were retrospectively examined. The patients’ operation side and contralateral axillary vein diameter and the difference between them, axillary vein flow rate and the difference between them, axillary vein wall thickness and the difference between them, severity of lymphedema, extremity joint restriction examination, and the Nottingham Health Profile (NHP) data were recorded. The relationship of these parameters with the lymph node dissection width and radiotherapy was analyzed. Results: Fifty-eight patients in total were included in the study. In the distribution of lymphedema and lymphedema severity according to ALND groups, there is a statistically significant difference (p < 0.001). A statistically significant difference was determined in the distribution of the difference in the axillary vein blood flow rate and axillary vein diameter difference between the two arms according to the lymph node dissection groups. In the distribution of physical therapy and rehabilitation scales according to the lymph node dissection groups, a significant difference was found in the disabilities of the arm, shoulder, and hand (DASH), shoulder flexion restriction variables, and NHP sleep variables (all p < 0.001). Conclusions: This study demonstrated that ALND leads to more pronounced physiological and pathological changes in axillary venous structures—including increased vein wall thickness, altered flow rates, and diameter differences—compared to SLNB combined with breast-conserving surgery. These changes may be attributed to lymphovenous disruption and postoperative edema. Furthermore, radiotherapy appears to contribute to these changes, though to a lesser extent than ALND. Therefore, SLNB followed by radiotherapy may be preferable in eligible patients to reduce postoperative complications such as lymphedema, joint restriction, and sleep disturbances.